Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-02-26T16:40:29+01:00
Bonjour, 

E=  3(2x - 1) - (2x - 1)(2x + 1) --> identité remarquable (a+b)(a-b) = a²-b²
E= 6x - 3 - (4x²-1)
E= 6x - 3 - 4x² + 1
E= -4x² + 6x - 2

F= (3x - 2)² - (3x - 2)(2x - 3)
F= 9x² - 12x + 4 - (6x² - 9x - 4x + 6)
F= 9x² - 12x + 4 - 6x² + 9x + 4x - 6
F= 3x² + x - 2

G= (3x + 1)² + (2x - 3)(3x + 1)
G= 9x² + 6x + 1 + 6x² + 2x - 9x - 3
G= 15x² - x - 2

Bonne journée :)
2014-02-26T16:41:27+01:00
Bonjour

E=   3 (2x-1) - (2x-1) (2x+1)
E = 6x -3 - (4x² +2x -2x -1)
E = 6x -3 -4x² -2x+2x+1
E = -4x² +6x -2

F=   (3x-2)² - (3x-2) (2x-3)
F = 9x² -12x +4 - (6x² -9x -4x +6)
F = 9x² -12x +4 -6x² +9x +4x -6
F = 3x² +x -2

G=   (3x+1)² + (2x-3) (3x+1)

G = 9x² +6x +1 +6x² +2x -9x -3
G = 15x² -x -2